Butterfly wing color made of pigmented liquid - Kenji Nishida; Haruhiko Adachi; Minoru Moriyama; Ryo Futahashi; Paul E. Hanson; Shigeru Kondo (Cell Reports, 2023)
Summary: A previously undescribed mechanism underlying butterfly wing coloration patterns was discovered in two distantly related butterfly species, Siproeta stelenes and Philaethria diatonica. These butterflies have bright green wings, but the color pattern is not derived from solid pigments or nanostructures of the scales or from the color of the cuticular membrane but rather from a liquid retained in the wing membrane. Wing structure differs between the green and non-green areas. In the non-green region, the upper and lower cuticular membranes are attached to each other, whereas in the green region, we observed a space of 5–10 μm where green liquid is held and living cells are present. A pigment analysis and tracer experiment revealed that the color of the liquid is derived from hemolymph components, bilin and carotenoid pigments. This discovery broadens our understanding of the diverse ways in which butterfly wings obtain their coloration and patterns.